2017
DOI: 10.1530/erc-17-0095
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 2α and thymidylate synthase expression in adrenocortical cancer

Abstract: Topoisomerase II alpha (TOP2A) and thymidylate synthase (TS) are known prognostic parameters in several tumors and also predictors of efficacy of anthracyclines, topoisomerase inhibitors and fluoropirimidines, respectively. Expression of and mRNA was assessed in 98 patients with adrenocortical carcinoma (ACC) and protein expression was assessed by immunohistochemistry in a subset of 39 tumors. Ninety-two patients were radically resected for stage II-III disease and 38 of them received adjuvant mitotane. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…The chemotherapy protocol that is most effective in human ACCs is the combination of etoposide, doxorubicin and cisplatin with mitotane (EDP‐M) . Of these, etoposide and doxorubicin are topoisomerase II inhibitors, and a recent study showed that the level of TOP2A expression in human ACCs is predictive of the response to the EDP‐M chemotherapy protocol . In view of the prognostic relevance of TOP2A in canine ACTs, topoisomerase II inhibitors could be an interesting treatment to improve the prognosis of dogs with high intra‐tumoural TOP2A expression.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The chemotherapy protocol that is most effective in human ACCs is the combination of etoposide, doxorubicin and cisplatin with mitotane (EDP‐M) . Of these, etoposide and doxorubicin are topoisomerase II inhibitors, and a recent study showed that the level of TOP2A expression in human ACCs is predictive of the response to the EDP‐M chemotherapy protocol . In view of the prognostic relevance of TOP2A in canine ACTs, topoisomerase II inhibitors could be an interesting treatment to improve the prognosis of dogs with high intra‐tumoural TOP2A expression.…”
Section: Discussionsupporting
confidence: 59%
“…TOP2A is predominantly associated with proliferating cells, which makes it an interesting therapeutic target in cancer. TOP2A is also a prognostic marker in human ACCs and other tumour types . Several TOP2A inhibitors are therefore successfully used in the clinic as anticancer drugs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High RRM1 expression levels are associated with reduced DFS and OS (Volante et al 2012); • Topoisomerase II alpha (TOP2A) is an enzyme responsible for transcription, replication and chromosome condensation and segregation during cell division. High TOP2A expression is correlated with longer time for progression after etoposidedoxorubicin -cisplatin -mitotane (EDP-M) treatment (Roca et al 2017).…”
Section: Molecular Markers Reveal Disease Mechanisms and Improve Patimentioning
confidence: 99%
“…Moreover, the level of immunoreactive CYP2W1 in tumors is associated with hormoneactivity,amoredifferentiatedphenotype,and in cancer, with a better response to mitotane treatment. These findings allow considering CYP2W1 as a possible marker to prognose tumor response to mitotane used as an adjuvant or palliative therapy aftersurgery.TheactivityoftopoisomeraseIIαand thymidylate synthase as prognostic criteria was analyzed in [14]. The activity of these enzymes in tumor tissuewasfoundnottobeassociatedwiththeeffect of mitotane.…”
mentioning
confidence: 99%